Highly Selective and Stable NiSn/SiO2 Catalyst for Isobutane Dehydrogenation: Effects of Sn Addition. Issue 19 (8th September 2016) - Wang, Guowei; Wang, Haoren; Zhang, Huanling; Zhu, Qingqing; Li, Chunyi; Shan, Honghong
Abstract: Ni/SiO2 catalysts with large surface area Ni particles exhibit high hydrogenolysis activity, leading to the formation of large amounts of methane and coke. To destroy the active sites for hydrogenolysis, namely the aggregated Ni ensembles, Sn species were introduced into the Ni/SiO2 catalyst. As expected, isobutene selectivity was significantly increased to 90.2 %. The promoting role of Sn on the dehydrogenation performance could be interpreted as both a geometric and electronic effect. On one hand, Sn addition efficiently dispersed aggregated Ni particles and reduced Ni particle size from 77 to 16 nm, weakening the ability of Ni for C−C bond rupture. On the other hand, additional electrons provided by Sn led to a high electronic density of Ni, facilitating the desorption of isobutene from the catalyst and suppressing secondary reactions. Consequently, coke formation was effectively inhibited over the NiSn/SiO2 catalyst, further guaranteeing a good stability and prolonged cycle time. Abstract : Effectively separated : The promoting mechanism of Sn addition to Ni/SiO2 catalysts was interpreted as a result of geometric and electronic effects. On one hand, Sn addition dispersed aggregated Ni particles effectively, breaking the active sites for hydrogenolysis. On the other hand, additional electrons provided by Sn led to a high electronic density of Ni, facilitating the desorption of isobutene and suppressing secondary reactions.